The effect of lutein on vancomycin-induced oxidative kidney damage in rats (Annals of Medical Research, 2021)
Aim: It has been reported that nephrotoxicity is observed in 5-25% of patients during vancomycin use. The part oxidative stress plays in the pathogenesis of vancomycin-induced nephrotoxicity has been demonstrated. Lutein shows antioxidant activity. The purpose of the present study was to evaluate effects experienced by lutein on oxidative kidney damage induced by vancomycin in rats biochemically an histopathologically.Materials and Methods: Oral administration of lutein at a rate of 1mg per kg was performed for the lutein plus vancomycin group (L+VAN) (n=6), whereas saline was administered to the vancomycin (VAN) (n=6) and healthy control (C) (n=6) groups. Sixty minutes after administration of lutein and solvent, 200 mg/kg vancomycin was intraperitoneally injected twice a day to L+VAN and VAN groups. This procedure was repeated for 7 days. Then malondialdehyde (MDA), total glutathione (tGSH), total oxidant system (TOS) and total antioxidant system (TAS) levels have been assessed in kidney tissues; in addition, creatinine and BUN were measured in blood samples. Kidney tissues were also evaluated histopathologically.Results: Significant histopathological damage could be seen in the kidney tissue of the VAN group that increasing MDA and TOS and creatinine and BUN. Histopathological damage was not very significant in the L+VAN group that decreasing MDA, TOS, BUN and creatinine levels.Conclusion: This suggests that lutein may be effective for the treatment of the treatment of vancomycin-associated oxidative kidney damage.